La sociologie et les Sciences de la Société - Dussault, Gilles (Relations industrielles / Industrial Relations, 1977)
This article reviews "La sociologie et les Sciences de la Société" created under the direction of Jean Cazeneuve.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z